Static Stiffness Analysis of a New Scissor-type Telescoping and Lifting Mechanism - Hao Gang; Chang Boyan; Li Wenqi (Jixie chuandong)
Combining hart straight-line mechanism with scissors mechanism,a new type of deployable model in straight-line motion which consists of revolute joint only is proposed. Corresponding modular system named scissor-type telescoping and lifting mechanism（ STLM） is designed for achieving straight-line motion in one dimension. Firstly,modular principle of STLM is explained and the composition of the mechanism is equivalent to the sequential stacking of three kinds of modules including bottom module,middle module and top module. These modules are all composed by the deployable model. Secondly,the kinematics equations of single deployable model is established and introduced into constructing the whole kinematics equations with multi-layer modules which can be used to validate the proposed method for achieving straight-line motion. Finally,taking STLM consisted with three-layer and two-row modules as an example,the structural behavior of static stiffness for this mechanism is analyzed by simulation. Results show a good performance in the stiffness along the deployable direction.